Impact of 3D surface scanning protocols on the Os coxae digital data: Implications for sex and age-at-death assessment - Kotěrová, Anežka; Králík, Vlastimil; Rmoutilová, Rebeka; Friedl, Lukáš; Růžička, Pavel; Velemínská, Jana; Marchal, François; Brůžek, Jaroslav (Journal of forensic and legal medicine, 2019)
The 3D imaging technologies have become of paramount importance for example in disciplines such as forensic anthropology and bioarchaeology, where they are being used more and more frequently. There are several new possibilities that they offer; for instance, the easier and faster sharing of data among institutions, the possibility of permanent documentation, or new opportunities of data analysis. An important requirement, however, is whether the data obtained from different scanning devices are comparable and whether the possible varying outputs could affect further analyses, such as the estimation of the biological profile. Therefore, we aimed to investigate two important questions: (1) whether 3D models acquired by two different scanning technologies (structured light and laser) are comparable and (2) whether the scanning equipment has an effect on the anthropological analyses, such as age-at-death estimation and sex assessment. 3D models of ossa coxa (n = 29) were acquired by laser (NextEngine) and structured light (HP 3D Structured Light Scanner PRO 2) scanners. The resulting 3D models from both scanners were subjected to age-at-death analyses (via the quantitative method of Stoyanova et al., 2017) and sex analyses (via Diagnose Sexuelle Probabiliste 2 of Brůžek et al., 2017). Furthermore, high quality scans of a small sample (n = 5) of pubic symphyseal surfaces with the RedLux Profiler device were acquired as reference surfaces to which the outputs from both scanners were compared. Small deviations between surfaces were more evident in more rugged surfaces (in areas of depression and protrusion). Even though small differences from the reference surfaces were found, they did not have a significant effect on the age and sex estimates. It never resulted in the opposite sex assignment, and no significant differences were observed between age estimates (with the exception of those with the TPS/BE model).
Keywords: Sex Determination by Skeleton; lasery; zobrazování trojrozměrné; Male; soudní antropologie; určení pohlaví podle kostry; Lasers; Age Determination by Skeleton; regresní analýza; Forensic Anthropology; určení kostního věku; Structured light technology; Computer Simulation; Observer Variation; mužské pohlaví; Imaging, Three-Dimensional; RedLux profiler; Os coxae; pánevní kosti; Laser scanning; Biological profile; Age and sex estimation; odchylka pozorovatele; lidé; ženské pohlaví; Humans; počítačová simulace; Regression Analysis; Pelvic Bones; Female